Promising bioactive metabolites of mangrove inhabitant Streptomyces tauricus and prostate cancer PC3 cell inhibition by antimicrobial peptides - Karthik, Yalpi; Kalyani, Manjula Ishwara; Krishnappa, Srinivasa; Ramakrishna, Krishnaveni; Sayed, Samy M.; Aharthy, Ohud Muslat; Alhelaify, Seham Sater; Mushtaq, Muntazir (Frontiers in Microbiology, 2023)
Streptomyces is a group of microbes known for antibiotic production and have contributed to more than 70 % of present commercially available antibiotics. These antibiotics are important in the management, protection, and treatment of chronic illnesses. In the present study, we could able to isolate the Streptomyces tauricus strain with accession number MW785875.1 from mangrove soil in Mangalore, India. After optimized growth conditions for Streptomyces tauricus on starch-casein agar medium, the mycelial and spore arrangements of S. tauricus were visualized through FESEM analysis. The culture phenotype included brown pigmentation, filamentous mycelia, and ash-colored spore production was observed. The GC/MS analysis of S. tauricus intracellular extract detected bioactive compounds reported for pharmacological applications. When compared to the NIST library, the majority of bioactive compounds identified in intracellular extract had molecular weights less than 1 mole-1. On the PC3 cell line, the Sephadex G-10 partially purified eluted peak protein fraction demonstrated significant anticancer activity. whereas LCMS analysis revealed the presence of Tryprostatin B, Fumonisin B1, Microcystin LR, and Surfactin C with molecular weights below 1Kda. This study found that small molecular weight microbial compounds are more effective in a variety of biological applications.